(untitled) - Richard P Feynman (London, 1992)
The book draws out the themes common to Law of Gravitation and the great unfolding discoveries of Newton, Maxwell and Einstein. It examines mathematics as the language of nature, the underlying principles of conservation and symmetry, the starting fact that time never goes backwards, and the probabilities and uncertainties introduced by quantum mechanics
Keywords: physics